Relationship between upper and lower limb conduit artery vasodilator function in humans - Thijssen, Dick H. J. (American Physiological Society, 2011)
Brachial artery flow-mediated dilation (FMD) is a strong predictor of future cardiovascular disease and is believed to represent a “barometer” of systemic endothelial health. Although a recent study [Padilla et al. Exp Biol Med (Maywood) 235: 1287–1291, 2010] in pigs confirmed a strong correlation between brachial and femoral artery endothelial function, it is unclear to what extent brachial artery FMD represents a systemic index of endothelial function in humans. We conducted a retrospective analysis of data from our laboratory to evaluate relationships between the upper (i.e., brachial artery) vs. lower limb (superficial femoral n = 75; popliteal artery n = 32) endothelium-dependent FMD and endothelium-independent glyceryl trinitrate (GTN)-mediated dilation in young, healthy individuals. We also examined the relationship between FMD assessed in both brachial arteries (n = 42). There was no correlation between brachial and superficial femoral artery FMD (r(2) = 0.008; P = 0.46) or between brachial and popliteal artery FMD (r(2) = 0.003; P = 0.78). However, a correlation was observed in FMD between both brachial arteries (r(2) = 0.34; P < 0.001). Brachial and superficial femoral artery GTN were modestly correlated (r(2) = 0.13; P = 0.007), but brachial and popliteal artery GTN responses were not (r(2) = 0.08; P = 0.11). Collectively, these data indicate that conduit artery vasodilator function in the upper limbs (of healthy humans) is not predictive of that in the lower limbs, whereas measurement of FMD in one arm appears to be predictive of FMD in the other. These data do not support the hypothesis that brachial artery FMD in healthy humans represents a systemic index of endothelial function.